PENGETAHUAN PSIKOLOGI OLAHRAGA PADA PELATIH RENANG INDONESIA - Juriana, Juriana; Tahki, Kurnia; Zulfitranto, Gerdy (Universitas Negeri Jakarta, 2018)
This study aims to determine the level of knowledge about the sport psychology which is owned by the swimming coach in Indonesia. Data is collected at the time of Kejuaraan Renang Antar Perkumpulan Se-Indonesia (KRAPSI) held in Surabaya, East Java on December 2016. This study used incidental sampling technique with the number of 76 coaches. The instrument used in this study a questionnaire that had been tested for validity (0,360-0,756) and reliability (r=0,713). Data were analyzed using descriptive statistics for each dimension of sports psychology knowledge. Results of the research about knowledge of sports psychology owned by swimming coach is the following : a) Most of the swimming coach in Indonesia have high knowledge about developmental psychology (85.53%); b) Most of the swimming coach in Indonesia have high knowledge about learning psychology (71.05%); c) Most of the swimming coach in Indonesia have high knowledge about personality psychology (73.68%); d) Most of the swimming coach in Indonesia have high knowledge about social psychology (90.79%); e) Most of the swimming coach in Indonesia have high knowledge about the psychometric (72.37%).